Unraveling the role of histone acetylation in sepsis biomarker discovery - Cheng, Feng; Deng, Juxin; Du, Zhaoyang; Li, Lei; Qiu, Zhaolei; Zhu, Min; Zhao, Hongchang; Wang, Zhenjie (Frontiers in Molecular Biosciences, 2025)
IntroductionSepsis is a life-threatening condition caused by a dysregulated immune response to infection. Despite advances in clinical care, effective biomarkers for early diagnosis and prognosis remain lacking. Emerging evidence suggests that histone acetylation plays a crucial role in the pathophysiology of sepsis.MethodsTranscriptomic and single-cell RNA sequencing data were used to identify histone acetylation-related genes. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were performed, followed by machine learning algorithms (LASSO, SVM-RFE, and Boruta) to screen for potential biomarkers. Mendelian randomization (MR), RT-qPCR, and functional assays were conducted for validation.ResultsBLOC1S1, NDUFA1, and SFT2D1 were identified as key biomarkers. A predictive nomogram demonstrated strong diagnostic potential. Immune infiltration and single-cell analyses linked the biomarkers to macrophage activity. MR analysis confirmed SFT2D1 as a causal factor in sepsis. Functional assays showed that knockdown of SFT2D1 suppressed CXCL10 and IL-6 expression, indicating its pro-inflammatory role.DiscussionThis study identifies novel biomarkers associated with histone acetylation and immune dysregulation in sepsis. These findings deepen our understanding of sepsis pathogenesis and may facilitate the development of improved diagnostic and therapeutic strategies.